Paru Dheko (Kawin Lari) Pada Masyarakat Desa Nabe (Ende Lio) dan Implikasinya Bagi Bimbingan dan Konseling Keluarga Tahun 2025 - Magdalena Nelcia Mite; Kristinus Sembiring; Dhiu Margaretha (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
As a way to transition between traditional values ​​and individual freedom in choosing a partner, this study examines the phenomenon of Paru Dheko (elopement), which is still common in Nabe Village, Maukaro District, Ende Regency. The purpose of this study is to examine the causes of Paru Dheko and its impact on the community, as well as its impact on culturally based family consultation and counseling services in the surrounding area. The methodology used in this study is descriptive qualitative, with 20 participants consisting of traditional leaders, village officials, and Paru Dheko actors. Miles and Huberman's interactive model was used to analyze data collected from semi-structured interviews, observations, and document studies. The findings indicate that premarital pregnancy (10%), financial constraints (25%), differences in lineage (30%), and lack of parental consent (35%) are the main causes of Paru Dheko. Although the majority of the community believes that Paru Dheko is contrary to traditional and religious values, some still consider it a solution in certain social situations. This incident, which impacts family harmony and the symbolic value of dowries, represents a conflict between traditional values ​​and the needs of contemporary society. This study highlights the need for culturally specific family counseling services in indigenous communities to foster intergenerational communication and prevent nontraditional marriage practices.